Fast-varying time lags in the quasi-periodic oscillation in GRS 1915 + 105 - Belloni, Tomaso M (2024)
The properties of subsecond time variability of the X-ray emission of the black hole binary GRS 1915 + 105 are very complex and strictly connected to its patterns of variability observed on long time-scales. A key aspect for determining the geometry of the accretion flow is the study of time lags between emission at different energies, as they are associated to key time-scales of the system. In particular, it is important to examine the lags associated to the strong low-frequency quasi-periodic oscillations (QPOs), as the QPOs provide unambiguous special frequencies to sample the variability. We have analysed data from an observation with the AstroSat satellite, in which the frequency of the low-frequency QPO varies smoothly between 2.5 and 6.6 Hz on a time-scale of ∼10 h. The derived phase lags show the same properties and evolution of those observed on time-scales of a few hundred days, indicating that changes in the system geometry can take place on times below one day. We fit selected energy spectra of the source and rms and phase-lag spectra of the QPO with a time-variable Comptonization model, as done previously to RossiXTE data of the same source, and find that indeed the derived parameters match those obtained for variations on much longer time-scales.